Berberine enhances inhibition of glioma tumor cell migration and invasiveness mediated by arsenic trioxide - Lin, Tseng-Hsi (BioMed Central, 2008)
BACKGROUND: Arsenic trioxide (As(2)O(3)) exhibits promising anticarcinogenic activity in acute promyelocytic leukemic patients and induces apoptosis in various tumor cells in vitro. Here, we investigated the effect of the natural alkaloid berberine on As(2)O(3)-mediated inhibition of cancer cell migration using rat and human glioma cell lines. METHODS: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used to determine the viability of rat C6 and human U-87 glioma cells after treatment with As(2)O(3 )or berberine, and after co-treatment with As(2)O(3 )and berberine. The wound scratch and Boyden chamber assays were applied to determine the effect of As(2)O(3 )and berberine on the migration capacity and invasiveness of glioma cancer cells. Zymography and Western blot analyses provided information on the effect of As(2)O(3 )and berberine on the intracellular translocation and activation of protein kinase C (PKC), and some PKC-related downstream factors. Most assays were performed three times, independently, and data were analyzed using ANOVA. RESULTS: The cell viability studies demonstrated that berberine enhances As(2)O(3)-mediated inhibition of glioma cell growth after 24 h incubation. Untreated control cells formed a confluent layer, the formation of which was inhibited upon incubation with 5 μM As(2)O(3). The latter effect was even more pronounced in the presence of 10 μM berberine. The As(2)O(3)-mediated reduction in motility and invasion of glioma cells was enhanced upon co-treatment with berberine. Furthermore, it has been reported that PKC isoforms influence the morphology of the actin cytoskeleton, as well as the activation of metalloproteases MT1-MMP and MMP-2, reported to be involved in cancer cell migration. Treatment of glioma cells with As(2)O(3 )and berberine significantly decreased the activation of PKC α and ε and led to actin cytoskeleton rearrangements. The levels of two downstream transcription factors, myc and jun, and MT1-MMP and MMP-2 were also significantly reduced. CONCLUSION: Upon co-treatment of glioma cells with As(2)O(3 )and berberine, cancer cell metastasis can be significantly inhibited, most likely by blocking the PKC-mediated signaling pathway involved in cancer cell migration. This study is potentially interesting for the development of novel chemotherapeutic approaches in the treatment of malignant gliomas and cancer development in general.